Copper-transfer mechanism from the human chaperone Atox1 to a metal-binding domain of wilson disease protein - Rodriguez-Granillo, Agustina (2010)
The molecular details of how copper (Cu) is transferred from the human Cu chaperone Atox1 to metalbinding domains (MBDs) of P1B-type ATPases are still unclear. Here, we use a computational approach, employing quantum mechanics/molecular mechanics (QM/MM) methods, to shed light on the reaction mechanism [probable intermediates, Cu(I) coordination geometries, activation barriers, and energetics] of Cu(I) transfer from Atox1 to the fourth MBD of Wilson disease protein (WD4). Both Atox1 and WD4 have solvent-exposed metal-binding motifs with two Cys residues that coordinate Cu(I). After assessing the existence of all possible 2-, 3- and 4-coordinate Cu-intermediate species, one dominant reaction path emerged. First, without activation barrier, WD4's Cys1 binds Cu(I) in Atox1 to form a 3-coordinated intermediate. Next, with an activation barrier of about 9.5 kcal/mol, a second 3-coordinated intermediate forms that involves both of the Cys residues in WD4 and Cys1 of Atox1. This species can then form the product by decoordination of Atox1's Cys1 (barrier of about 8 kcal/mol). Overall, the Cu-transfer reaction from Atox1 to WD4 appears to be kinetically accessible but less energetically favorable (△E = 7.7 kcal/mol). Our results provide unique insights into the molecular mechanism of protein-mediated Cu(I) transfer in the secretory pathway and are in agreement with existing experimental data. © 2010 American Chemical Society.